2014
DOI: 10.5539/mas.v8n6p161
|View full text |Cite
|
Sign up to set email alerts
|

Academic Researchers’ Absorptive Capacity Influence on Collaborative Technologies Acceptance for Research Purpose: Pilot Study

Abstract: A wide variety of Collaborative Technologies (CT) emerged to facilitate the collaboration among peers. Despite the extensive literature of CT adoption in various contexts, a massive lack exists in CT adoption by academic researchers. Consequently, this study concerns the CT adoption by academic researchers. The study investigates how academic researchers' Absorptive Capacity (ACAP) impacts the acceptance of CT for research purpose. The authors have extended Technology Acceptance Model (TAM) to explain how acad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
0
1
0
Order By: Relevance
“…A conceptual model is a well-specified model showing the fundamental relationships of a given set of variables as hypothesized from the theory [172]. Guba and Lincoln [173] adapted the view by Bamasoud [174], which found in his study that, if the following points are taken into consideration, i.e., the objective reality can be systematically and rationally investigated empirically and guided by the laws applied to social science; the independency of the researcher and the phenomenon being studied; the researcher remains detached; neutral objective; and propositions are generated by theories that are operationalized as hypotheses and have undergone experimental testing that is replicable, then the research is categorized as positivist.…”
Section: The Proposed Cyberstalking Victimization Conceptual Modelmentioning
confidence: 99%
“…A conceptual model is a well-specified model showing the fundamental relationships of a given set of variables as hypothesized from the theory [172]. Guba and Lincoln [173] adapted the view by Bamasoud [174], which found in his study that, if the following points are taken into consideration, i.e., the objective reality can be systematically and rationally investigated empirically and guided by the laws applied to social science; the independency of the researcher and the phenomenon being studied; the researcher remains detached; neutral objective; and propositions are generated by theories that are operationalized as hypotheses and have undergone experimental testing that is replicable, then the research is categorized as positivist.…”
Section: The Proposed Cyberstalking Victimization Conceptual Modelmentioning
confidence: 99%
“…In [13] revealed that the usage of smartphones positively influence the academic researchers' research activities. In [14] ascertained that smartphones play affirmative role in delivery service sector.…”
Section: 2smartphonesmentioning
confidence: 99%